HUBUNGAN KERJA KEPALA DESA DENGAN LEMBAGA ADAT DESA DALAM PENYELENGGARAAN PEMERINTAHAN DESA (STUDI KASUS DI DESA OJANDETUN KABUPATEN FLORES TIMUR) - Onan, Yulius Charlos Gate; Djaha, Ajis Salim Adang; Andayana, Made Ngurah Demi (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
This study explores the working relationship between village heads and traditional village institutions in village governance, with a focus on land conflict resolution, infrastructure development, and tourism promotion in Ojandetun Village, Flores Timur. Using a qualitative case study method, data were collected through interviews, observations, and documentation. The study reveals that both entities collaborate in different capacities through communication, coordination, partnership, and social control. However, issues such as weak coordination and administrative communication hinder the process. This paper emphasizes the importance of mutual understanding and regular dialogue between both parties to support effective governance.